Distress intolerance and withdrawal severity among daily smokers: The role of smoking abstinence expectancies. (December 2019) - Rosen, Rachel L.; Borges, Allison M.; Kibbey, Mindy M.; Steinberg, Marc L.; Leyro, Teresa M.; Farris, Samantha G.
Abstract: Background: Distress intolerance (DI), the perceived inability to withstand distress, is implicated in cigarette smoking maintenance. Greater DI may contribute to anticipation of negative outcomes from smoking abstinence, which in turn could contribute to withdrawal symptom severity. The current study aimed to evaluate (1) the association between DI and acute abstinence expectancies and (2) the potential mediating role of abstinence expectancies in the relationship between DI and withdrawal symptom severity. Method: Participants ( n  = 444) were daily smokers who reported at least one prior quit attempt, participating in a larger online study on distress and smoking. DI, subjective nicotine withdrawal, and smoking abstinence expectancies were assessed using the Distress Tolerance Scale (DTS), Minnesota Nicotine Withdrawal Scale (MNWS), and Smoking Abstinence Expectancies Questionnaire (SAEQ). Results: DTS was significantly negatively associated with SAEQ, specifically Negative Mood ( r  = −0.37, p  < .001), Somatic Symptoms ( r  = −0.47, p  < .001), and Harmful Consequences ( r  = −0.59, p  < .001) subscales, but was not associated with Positive Expectancies subscale ( r  = 0.05, p  = .31). Results indicated a significant effect of DTS on withdrawal symptom severity via SAEQ. Follow-up analyses indicated that the indirect effects were driven specifically by SAEQ Negative Mood and Harmful Consequences subscales. Discussion: DI is related to more negative abstinence expectancies, particularly affective aspects of abstinence, which may contribute to the severity of nicotine withdrawal symptoms. This study provides initial evidence of a specific cognitive process that may explain why DI contributes to heightened subjective experience of nicotine withdrawal symptoms. Highlights: DI is associated with more severe nicotine withdrawal symptoms. DI is associated with greater negative expectancies about acute smoking abstinence. Smoking abstinence expectancies indirectly predict the DI-withdrawal link.